RADIOPROTECTION QUALITY OF A NEW ORAL REMEDY "APIOR" UNDER CONDITIONS OF RADIATION STOMATITIS IN RATS - L.S. Kravchenko; S.A. Schnaider; Ya.F. Burdina (Ukrainian Medical Stomatological Academy, 2015)
Radiation stomatitis development is the basic problem in management of anti-cancer therapy in patients who had X-ray therapy associated with cancer at the region of head and neck. Prophylaxis and medical treatment of radiation defeats are not always effective. The purpose of the research is studying of the radioprotection quality of a new oral remedy "Apior" on the basis of api substance under conditions of radiation stomatitis in rats. Materials and methods. The experiment was conducted on 42 white rats. A clinical picture of radiation stomatitis in animals and influence of peroxidation protection of the saliva glands have been studied. Results: • Under experiment conditions the new gel "Apior" had a local protective action on the course of erosiveulcerous radiation stomatitis and assisted in healing the oral mucosa. • During of the experimental study there was a better clinical picture of radiation stomatitis and softer course of free radicals oxidation in saliva glands, especially when new gel was used. • The obtained results indicate the perspectiveness of the new oral agent application in case of medical treatment of erosive-ulcerous elements of radiation injury of the oral mucosa.